Особенности реакции генотипов сортов мягкой озимой пшеницы на регуляторы роста растений, предопределяющие величину показателя зимостойкости - Савкин, Н.Л.; Ковтун, Н.В.; Шелихов, П.В.; Маруха, Н.Н.; Павлова, М.В.; Пономарева, К.В. (Фактори експериментальної еволюції організмів, 2013)
Purpose. To define the reaction of soft winter wheat variety genotypes in varions agroekological groups and different selection сentres to the use of varions of plant growth regulators (P.G.R.) thet stipulate winter hardiness index. Technigues. We studied five variants with the use of P.G.R. such as Biohumus, Vympel, Vympel K, Orakul and Vympel K + Orakul, controlling is carried on P.G.R. in accordance with field experience technigues. Results. The pekuliarities of winter wheat variety genotypes reaction to the nature of winter hardiness index development when seeds are treated by plant growth regulators have been studied. Conclusions. Growth activating products encourage the increase of soft winter wheat hardiness. The nature of thе genotype reaction to the products studied is defined, first of all, by the genotype of the variety itself, dy thе plant growth regulators used, and by the interaction of the genotype set of weather factors.